POTENSI TEGAKAN KEMIRI (Aleurites moluccana (L.) Wild.) DALAM MENGENDALIKAN LIMPASAN PERMUKAAN DAN EROSI - Tewonto, Rai Adhi Masiakh; Naharuddin, Naharuddin; Sudhartono, Arif; Rosyid, Abdul (Jurnal Warta Rimba, 2020)
Candlenut plant (Aleurites moluccana Willd.) Is a multiple-purpose tree species. This plant is often found growing in various places in the Sigimpu region, Palolo District, Sigi Regency. The planting of candlenut trees has long been carried out by farmers in Sigimpu Village, both on land and village land. Various parties have promoted this activity with the aim of improving farmer welfare, environmental sustainability, and guaranteeing wood supply. This study aims to determine the condition of the vegetative stands of candlenut trees in several phases of ages 5, 10, and 15 years in their potential to control surface runoff and erosion. In its implementation, the development of candlenut plants should not only focus on production aspects or economic goals but also must consider environmental aspects, especially for the sake of controlling surface runoff and erosion. The study was conducted for 3 months, namely, from July to December 2018. The study was conducted on community forests, especially on candlenut plants aged 5, 10, and 15 years located in Sigimpu Village, Palolo District, Sigi Regency. The research procedures used were measurements of rainfall and observations of surface runoff and erosion. Surface runoff and erosion can be suppressed by using candlenut plants as vegetative soil conservation patterns. The smallest surface runoff occurred in 15-year-old candlenut plants at 87.675 liters and 5 years old at 598.297 liters, while controls (without candlenut plants) amounted to 1,245.321 liters The smallest erosion occurred in 15-year-old candlenut plants at 56.629 grams and high the age of 15 years is 132.274 grams, while the control (without candlenut plants) is 219.652 grams.